Nutritional contribution of street foods to the diet of people in developing countries: a systematic review. Issue 6 (17th May 2013) - Steyn, Nelia Patricia; Mchiza, Zandile; Hill, Jillian; Davids, Yul Derek; Venter, Irma; Hinrichsen, Enid; Opperman, Maretha; Rumbelow, Julien; Jacobs, Peter
Abstract Objective To review studies examining the nutritional value of street foods and their contribution to the diet of consumers in developing countries. Design The electronic databases PubMed/MEDLINE, Web of Science, Cochrane Library, Proquest Health and Science Direct were searched for articles on street foods in developing countries that included findings on nutritional value. Results From a total of 639 articles, twenty-three studies were retained since they met the inclusion criteria. In summary, daily energy intake from street foods in adults ranged from 13 % to 50 % of energy and in children from 13 % to 40 % of energy. Although the amounts differed from place to place, even at the lowest values of the percentage of energy intake range, energy from street foods made a significant contribution to the diet. Furthermore, the majority of studies suggest that street foods contributed significantly to the daily intake of protein, often at 50 % of the RDA. The data on fat and carbohydrate intakes are of some concern because of the assumed high contribution of street foods to the total intakes of fat, trans-fat, salt and sugar in numerous studies and their possible role in the development of obesity and non-communicable diseases. Few studies have provided data on the intake of micronutrients, but these tended to be high for Fe and vitamin A while low for Ca and thiamin. Conclusions Street foods make a significant contribution to energy and protein intakes of people in developing countries and their use should be encouraged if they are healthy traditional foods.